IMPLEMENTASI APLIKASI PERAWATAN ALAT ANGKUT TAMBANG PADA DIVISI PEMELIHARAAN DAN PERAWATAN PERUSAHAAN TAMBANG - Dwi Retnosari (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2018)
PT.Leighton Contarctors Indonesia is one of the mining companies engaged in the repair and maintenance of mining equipment. The current system is still using the old method of recording equipment damage every day still rely on reports from operational supervisors or operators who directly report the damage via HT radio (Hand Talk) so not infrequently the information collided with other information because very much users and make inaccurate data damage information and often cause errors in analyzing the damage to the conveyance equipment. In order to facilitate the smooth operation of operations in processing data repair and maintenance of mining equipment then PT.Leighton Contractors Indonesia to make an application using Borland Delphi 7 programming language using the MySQL database on Xampp. With the application is expected to facilitate the smooth operation of the company's operations in processing data repair and maintenance of mining equipment, and accelerate in obtaining information damage, repair and maintenance of mining equipment on every day. Keywords: Application, repair and maintenance, mining equipment, Delphi 7